2008
DOI: 10.1287/mnsc.1080.0877
|View full text |Cite
|
Sign up to set email alerts
|

Look Before You Leap: Market Opportunity Identification in Emerging Technology Firms

Abstract: Entrepreneurs play a fundamental role in bringing new technologies to market. Because technologies are often configurable to serve a variety of different markets, it is possible for entrepreneurs to identify multiple market opportunities prior to the first market entry of their emerging firms, and if they elect to do so, to therefore have a choice of which market to enter first. The empirical results presented in this paper offer three new insights regarding this important early-stage choice in new firm creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
287
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(310 citation statements)
references
References 43 publications
10
287
0
2
Order By: Relevance
“…University spin-offs often pursue several business models at the same time (Clausen and Rasmussen 2012). The market application of technological inventions and knowledge is rarely clear from the outset (Gruber et al 2008) and the business models are modified as entrepreneurs gain more knowledge about resources and potential opportunities (Chesbrough and Rosenbloom 2002).…”
Section: Opportunity Development Competencymentioning
confidence: 99%
“…University spin-offs often pursue several business models at the same time (Clausen and Rasmussen 2012). The market application of technological inventions and knowledge is rarely clear from the outset (Gruber et al 2008) and the business models are modified as entrepreneurs gain more knowledge about resources and potential opportunities (Chesbrough and Rosenbloom 2002).…”
Section: Opportunity Development Competencymentioning
confidence: 99%
“…Specifically, they need to draw on influencing, monitoring, and updating strategies to ensure that the emerging value proposition will evolve in such a way that control points through which the firm hopes to capture some of the created value can actually ever apply. Finally, we highlight how our insights may hold the potential to provide a fresh view toward combining more goal-oriented (Gruber et al, 2008(Gruber et al, , 2013McGrath & MacMillan, 2000) and more process-oriented (Baker & Nelson, 2005;Sarasvathy, 2001;Sarasvathy, Dew, Read, & Wiltbank, 2008) perspectives of entrepreneurship.…”
Section: Introductionmentioning
confidence: 98%
“…Such envisioning, however, is not always possible (Anderson, 1999;Dougherty & Dunne, 2011;Dunne & Dougherty, 2016), in particular not when built on generative technologiestechnologies which have the potential to produce unprompted change and to create a breathtaking variety of potential future applications (Gruber, MacMillan, & Thompson, 2008;Zittrain, 2006). For example, attempts to introduce new technologies at lower layers of the digital infrastructure (say, new chip standards to enable near-field communications for 'Internet of Things' applications) typically tend to enable such a large number of potential user-facing applications at upper layers that this can easily overwhelm prospective stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that an individual's experiences play an important role in his/her perception of the environment [38] and sustainability-oriented actions [14]. Therefore, we controlled for three types of entrepreneurial experience, namely management experience, marketing experience, and technology experience [72]. We included three firm-level control variables.…”
Section: Control Variablesmentioning
confidence: 99%